2008
DOI: 10.1007/s00431-008-0669-2
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with defecation patterns in 0–24-month-old children

Abstract: To identify the normal defecation patterns and the factors affecting these patterns in the first two years of life, a questionnaire was given to the parents of 1,021 children who were followed in a well-child clinic. The time of first meconium passage, presence of colic symptoms, frequency, color, and consistency of stools were recorded.Mann Whitney U, Wilcoxon, chi-square, and correlation tests were used in the statistical analyses. The median number of defecations per day was six in the first month of life. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
56
1
13

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(78 citation statements)
references
References 23 publications
8
56
1
13
Order By: Relevance
“…Fontana et al (8) studied a group of 188 infants under 3 months and found that daily stool count in breastfed, breastfed plus formula and formula only were 3.2, 2.4 and 2.0, respectively. Tunc et al (9) reported that stool frequency was higher in exclusively breastfed infants in 0-24 month-old children. Similarly, our study results supported the fact that breastfeeding enhances daily stool count especially in the first six months.…”
Section: Discussionmentioning
confidence: 97%
“…Fontana et al (8) studied a group of 188 infants under 3 months and found that daily stool count in breastfed, breastfed plus formula and formula only were 3.2, 2.4 and 2.0, respectively. Tunc et al (9) reported that stool frequency was higher in exclusively breastfed infants in 0-24 month-old children. Similarly, our study results supported the fact that breastfeeding enhances daily stool count especially in the first six months.…”
Section: Discussionmentioning
confidence: 97%
“…8 Ülkemizde 0-24 aylık bebekler üzerinde yürütülen çalışmada, bir, iki ve dört aylık bebeklerin beslenme şekli ile günlük dışkı sayıları arasında anlamlı fark bulunmuştur. 6 Çalışmaya göre, sadece anne sütü ile beslenen bebeklerin dışkı sayısı anne sütü ile beraber mama ile beslenenlerin dışkı sayı-sına göre daha fazladır ve bu fark altıncı ayda ortadan kalkmıştır. Bu çalışmada da sadece anne sütü ile beslenen bebekler, anne sütü ile beraber ek besin/ mama alanlara göre daha sık dışkılamakta-dır.…”
Section: Dişki Sayisiunclassified
“…6,15,24 Yaşla beraber dışkı renginin koyulaşması, bebeklerde ek besinlere başlanması ile açıklanmıştır. 8 Literatürden farklı olarak, çalışmamızda yaşla beraber dışkı renginde herhangi bir değişiklik olmamıştır.…”
Section: Dişki Rengi̇unclassified
See 2 more Smart Citations